The Effect of The Project-Based Learning Model Using 3D Creative Board Media on The Learning Outcomes - Darda, Abu; Aurellia, Bellamy Ava; Islam, Muhammad Thoriqul; Alim, Syaiful; Prayogi, Rizal Mifthakul; Rofik, Zainur (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
Islamic History is an important subject within Islamic Religious Education that aims to develop students’ historical understanding and Islamic values. However, the learning process is often dominated by teacher-centered lecture methods, resulting in low student engagement and suboptimal learning outcomes. This study aims to examine: (1) the effect of the lecture method on Islamic History learning outcomes of Grade VII A students as the control class, (2) the effect of the Project Based Learning (PjBL) model using 3D creative board media on the learning outcomes of Grade VII B students as the experimental class, and (3) the differences in learning outcomes between the two classes. This research employed a quantitative, quasi-experimental design with a non-equivalent control group. Data were collected through pre-tests and post tests and analysed using validity, reliability, normality, homogeneity, and hypothesis testing with SPSS version 25. The results showed that the lecture method improved students’ learning outcomes in the control class, with a mean pre-test score of 67.9 and a post-test score of 73.70, although the improvement was relatively low. In contrast, the experimental class taught using the PBL model supported by 3D creative board media demonstrated a more significant improvement, with a mean pre-test score of 50.85 and a post-test score of 83.75. Hypothesis testing revealed a significant difference between the two classes, as indicated by a p-value of 0.002 < 0.05. Therefore, the PBL model using 3D creative board media is more effective in improving students’ learning outcomes in Islamic History.